The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.21608/ejgc.2014.9930
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC VARIATION IN EGYPTIAN WHITE LUPIN (Lupinus albus L.) GENOTYPES BASED ON COMBINED DATA OF ISSR AND FLUORESCENCE-BASED AFLP MARKERS

Abstract: Eighteen Lupinus albus L. accessions were provided by the National Gene Bank (NGB), Agriculture Research Center (ARC), Giza, Egypt. Accession numbers, collection dates and sites are listed in Table (1). The two cultivars Giza 1 and Giza 2 were developed through individual selection from local landraces; Giza 1 is adapted for cultivation in northern region of Egypt, whereas Giza 2 is adapted for Upper Egypt region planting. Both cultivars are tolerant to wilt disease (Hefny, 2011). The local commercial varietie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In study of Raman et al (2008) using Intron-Targeted Amplified Polymorphisms (ITAPs), SSR motifs, and DArT markers reported that Australian cultivars and breeding lines were clustered and tended to be distinct from European landraces. EL-Sherif et al (2014) estimated genetic relationships among eighteen white lupin (Lupinus albus L.) genotypes, using ISSR and AFLP markers. They found that some genotypes represent a relation to their distribution position also Giza2 cultivar and landrace from Sohag are clustered together.…”
Section: Molecular Analysismentioning
confidence: 99%
“…In study of Raman et al (2008) using Intron-Targeted Amplified Polymorphisms (ITAPs), SSR motifs, and DArT markers reported that Australian cultivars and breeding lines were clustered and tended to be distinct from European landraces. EL-Sherif et al (2014) estimated genetic relationships among eighteen white lupin (Lupinus albus L.) genotypes, using ISSR and AFLP markers. They found that some genotypes represent a relation to their distribution position also Giza2 cultivar and landrace from Sohag are clustered together.…”
Section: Molecular Analysismentioning
confidence: 99%
“…The conservation and preservation of the genetic resources of this species were of crucial importance for the breeding programs related to the improvement of the cultivar composition in the white lupine (Raza and Jornsgard, 2005;El-Sherif et al, 2014).…”
Section: Introductionmentioning
confidence: 99%